PEMANFAATAN EUPATORIUM ODORATUM SEBAGAI INSEKTISIDA ALAMI PENGENDALI LALAT - Ni Sri Yuliani; Aven B. Oematan; Viktor Lenda; Gerson Y.I. Sakan (Partner, 2018)
Flies are vectors of various diseases in livestock. Eupatorium odoratum plants are bush plants that thrive and have antibacterial, antifungal and insecticidal activity. The purpose of this research is to know the effectiveness of Eupatorium odoratum extract as a natural insecticide, easy to get and safe. Flies were taken from the farmyard location, then grouped into 4 of 40 each per group. Flies were treated with Eupatorium odoratum extract at concentrations of 25%, 50% and 75%, while the controls were not treated. Observation of extract activity on flies mortality was taken within 3 hours, 6 hours to 12 hours after treatment. The data were analyzed descriptively and showed that the treatment result was not effective. Flies adapted in experimental cages do not get food (blood sucking activity at the host), so flies will die or flies can not survive outside the host's body.